2021
DOI: 10.1186/s43093-021-00077-6
|View full text |Cite
|
Sign up to set email alerts
|

Employee motivation and job performance: a study of basic school teachers in Ghana

Abstract: Motivation as a meaningful construct is a desire to satisfy a certain want and is a central pillar at the workplace. Thus, motivating employees adequately is a challenge as it has what it takes to define employee satisfaction at the workplace. In this study, we examine the relationship between job motivation factors and performance among teachers of basic schools in Ghana. The study employs a quantitative approach on a sample of 254 teachers from a population of 678 in the Effutu Municipality of Ghana, of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 28 publications
3
18
0
3
Order By: Relevance
“…Work motivation can be interpreted as a stimulus for employees to carry out their work (Forson et al, 2021). Good motivation has a positive impact on the performance of the employee and ultimately gives brilliant achievements.…”
Section: Work Motivationmentioning
confidence: 99%
“…Work motivation can be interpreted as a stimulus for employees to carry out their work (Forson et al, 2021). Good motivation has a positive impact on the performance of the employee and ultimately gives brilliant achievements.…”
Section: Work Motivationmentioning
confidence: 99%
“…Another informant also revealed that the evaluation results were obtained and then tried to get better in the future. The provision of motivation through evaluation has been carried out by many others because sometimes the results of the evaluation are accompanied by rewards to students (Panesar-Aguilar & Aguilar, 2017;Forson et al, 2021).…”
Section: Asking To Gain Understandingmentioning
confidence: 99%
“…Evidence from the results showed that the productivity of an organization could improve through the motivation and promotion of office managers. Forson, Ofosu-Dwamena, Opoku, and Adjavon (2021) in another similar study investigated the link between employee motivation and the performance of basic school teachers in Ghana. Using multiple regression and Analysis of Variance (ANOVA) methodologies on a sample of 254 teachers derived from 678 teachers in the Efutu Municipality of Ghana, the results showed that compensation package, environment, job design and performance management system had a significant relationship with performance of basic school teachers in Ghana.…”
Section: Empirical Literaturementioning
confidence: 99%